Some features of Rayleigh-Taylor convection in the mixing of ideal gas mixtures - Толепберген A.G.; Mukamedenkyzy , V. (Recent Contributions to Physics, 2025)
The paper deals with computer modeling of convective structures formation at isothermal mixing of three-component gas system on the basis of numerical experiments using ANSYS Fluent. The research aims to study the transition of the system from a diffusion regime to a convective regime and to analyze the stability of mechanical equilibrium in multicomponent gas systems. The scientific and practical significance lies in understanding mass transfer processes, which are crucial for applied tasks in thermophysics, energy, and environmental sciences. Investigating the characteristics of transitional processes enables the clarification of diffusion-convection interaction mechanisms and the development of recommendations for process optimization. The research methodology includes numerical modeling of mass transfer processes using the k-ω turbulence model and Stefan-Maxwell equations. Boundary conditions, computational grids, and modeling parameters were adapted to adequately describe the structural features of mixing and convective flows. The main results confirmed the effectiveness of ANSYS Fluent in modeling convective flows. The numerical data demonstrated good agreement with experimental results, indicating the model’s ability to account for the influence of convective flows. The value of this study lies in developing a numerical approach that enables a quantitative description of kinetic transitions between diffusion and convection. The practical significance of the work is its applicability to the study of mixing processes in complex gas systems, making it useful for technological and scientific advancements.